2020
DOI: 10.1016/j.omtn.2020.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Plasma tRNA Fragments Derived from 5′ Ends as Novel Diagnostic Biomarkers for Early-Stage Breast Cancer

Abstract: Small RNAs derived from tRNAs are attracting considerable attention; however, the effects of tRNA-derived fragments (tRFs) and tRNA halves (tiRNAs) as biomarkers have not been investigated in early-stage breast cancer (EBC). The study aimed to explore whether tRFs and tiRNAs could be detected in plasma and whether they could serve as diagnostic biomarkers. The study was conducted in four phases. Thirty tRFs and tiR-NAs were selected by high-throughput sequencing in screening phase and then assessed in training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…With independence on the mechanism of release, stability, and possible biological activity, it is worth mentioning that the high abundance of tRFs in biofluids has opened an active field of research in biomarker discovery. The biogenesis of stress linked tRFs is reflected in plasma, with altered profiles in diseases such as cancer ( Dhahbi et al, 2014 ; Wang et al, 2020 ) or epilepsy ( Hogg et al, 2019 ). This highlights the need to include these species in the definition of prognostic and/or diagnostic biosignatures.…”
Section: Discussionmentioning
confidence: 99%
“…With independence on the mechanism of release, stability, and possible biological activity, it is worth mentioning that the high abundance of tRFs in biofluids has opened an active field of research in biomarker discovery. The biogenesis of stress linked tRFs is reflected in plasma, with altered profiles in diseases such as cancer ( Dhahbi et al, 2014 ; Wang et al, 2020 ) or epilepsy ( Hogg et al, 2019 ). This highlights the need to include these species in the definition of prognostic and/or diagnostic biosignatures.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also agreed with Wang, Kuang, and Zhao et al These researchers reported a high diagnostic value of tRFs in early breast cancer, lung cancer, and prostate cancer. 26–28 We also found that the extracellular vesicles-derived tRF-1:30-Lys-CTT-1-M2 was significantly upregulated in the metastatic hypopharyngeal cancer patients as compared with the non-lung metastatic patients. That means tRF-1:30-Lys-CTT-1-M2 was able to differentiate between lung metastatic and non-lung metastatic hypopharyngeal cancer.…”
Section: Discussionmentioning
confidence: 53%
“…In this regard, there is a growing body of evidence linking tRFs with the post-transcriptional regulation of gene expression and RNA processing, as well as with the onset and progression of human malignancies, highlighting their value to be targeted either for the elucidation of disease driver events or the development of modern diagnostics and therapeutics [55]. Finally, the presence of tRFs in the bloodstream, that has been reported previously [29,[56][57][58] and confirmed by our present analysis, clearly supports future studies for exploring their clinical utility as non-invasive cancer markers.…”
Section: Discussionmentioning
confidence: 88%